Illustrated history of landscape design - Boults, Elizabeth (Wiley, 2010)
Includes bibliographical references and index.; Illustrated History of Landscape Design takes an optical sweep of the iconic landscapes constructed throughout the ages. Organized by century and geographic region, this highly visual reference uses hundreds of masterful pen-and-ink drawings to show how historical context and cultural connections can illuminate today's design possibilities. This guide includes: Storyboards, case studies, and visual narratives to portray spaces; Plan, section, and elevation drawings of key spaces; Summaries of design concepts, principles, and vocabularies; Historic and contemporary works of art that illuminate a specific era; and Descriptions of how the landscape has been shaped over time in response to human need." "Directing both students and practitioners along a visually stimulating timeline, Illustrated History of Landscape Design is a valuable educational tool as well as an endless source of inspiration